THE LABORAL HEALTH AND SAFETY CLIMATE MEASUREMENT - Melià, Josep Lluís; Sesé, Albert (Anales de Psicología / Annals of Psychology, 1999)
The aim of this paper is to examine the psychometric properties and factorial structure of a selfadministered Safety Climate Questionnaire (C3/15). Organizational Safety Climate was defined as a set of organizational actions developed by the management, perceived by the workers and affecting its behaviors. The C3/15 Questionnaire was administered to a sample of 429 workers, belonging to industries provided by the colaboration of an Insurance Company and randomly drawn from the exhaustive accident records of Local Government. 1/3 of the original sample was deleted because of missing values, obtaining a final sample with 316 workers. Exploratory results show a realible and valid questionnaire with a three-dimensional structure: I) Safety Structures, II) Safety Policy, and III) Safety Actions.